Clinical approach on challenge and desensitization procedures with aspirin in patients with ischemic heart disease and nonsteroidal anti‐inflammatory drug hypersensitivity. Issue 3 (28th November 2016) - Cortellini, G.; Romano, A.; Santucci, A.; Barbaud, A.; Bavbek, S.; Bignardi, D.; Blanca, M.; Bonadonna, P.; Costantino, M. T.; Laguna, J. J.; Lombardo, C.; Losappio, L.M.; et al.
Abstract: Background: Hypersensitivity to acetylsalicylic acid (ASA) constitutes a serious problem for subjects with coronary artery disease. In such subjects, physicians have to choose the more appropriate procedure between challenge and desensitization. As the literature on this issue is sparse, this study aimed to establish in these subjects clinical criteria for eligibility for an ASA challenge and/or desensitization. Methods: Collection and analysis of data on ASA challenges and desensitizations from 10 allergy centers, as well as consensus among the related physicians and an expert panel. Results: Altogether, 310 subjects were assessed; 217 had histories of urticaria/angioedema, 50 of anaphylaxis, 26 of nonimmediate cutaneous eruptions, and 17 of bronchospasm related to ASA/nonsteroidal anti‐inflammatory drugs (NSAID) intake. Specifically, 119 subjects had index reactions to ASA doses lower than 300 mg. Of the 310 subjects, 138 had an acute coronary syndrome (ACS), 101 of whom underwent desensitizations, whereas 172 suffered from a chronic ischemic heart disease (CIHD), 126 of whom underwent challenges. Overall, 163 subjects underwent challenges and 147 subjects underwent desensitizations; 86 of the latter had index reactions to ASA doses of 300 mg or less. Ten subjects reacted to challenges, seven at doses up to 500 mg, three at a cumulative dose of 110 mg. The desensitization failure rate was 1.4%. Conclusions: In patients with stable CIHD and histories of nonsevere hypersensitivity reactions to ASA/NSAIDs, an ASA challenge is advisable. Patients with an ACS and histories of hypersensitivity reactions to ASA, especially following doses lower than 100 mg, should directly undergo desensitization.